2012
DOI: 10.1016/j.jom.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between supplier integration and time‐to‐market

Abstract: Recent operations management and innovation management research emphasizes the importance of supplier integration. However, the empirical results as to the relationship between supplier integration and time‐to‐market are ambivalent. To understand this important relationship, we incorporate two major recent developments. First, the literature has started to redefine supplier integration into two dimensions, supplier product integration and supplier process integration. Second, recent research has begun to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 121 publications
(217 reference statements)
6
113
3
Order By: Relevance
“…Wynstra et al, 2003;Schiele, 2010), but that companies purchasing locally fail to reap the benefits is more surprising. That supplier integration is associated with shorter TTM has also been well documented by previous empirical studies (Lau et al, 2010;Schiele, 2010;Perols et al, 2013). The surprise is again that this association is only valid for firms purchasing globally.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Wynstra et al, 2003;Schiele, 2010), but that companies purchasing locally fail to reap the benefits is more surprising. That supplier integration is associated with shorter TTM has also been well documented by previous empirical studies (Lau et al, 2010;Schiele, 2010;Perols et al, 2013). The surprise is again that this association is only valid for firms purchasing globally.…”
Section: Discussionsupporting
confidence: 71%
“…Other studies have also found that supplier integration is required for harnessing the innovation potential of new suppliers when outsourcing manufacturing (Bengtsson et al, 2009). Perols et al (2013) found that supplier integration in NPD is effective for improvements in TTM. Other studies have found that logistics-related integration has an impact on company performance, including product innovation (Flynn et al, 2010;Prajogo and Olhager, 2012).…”
mentioning
confidence: 97%
“…In order to assess goodness of fit Tenenhaus et al [83] proposes assessing R 2 with a suggested cut-off value of 0.36 [84]. Our model exceeds the rigid cut-off with an R 2 value of 0.46.…”
Section: Innovationmentioning
confidence: 99%
“…Although our sample size is not large enough to use these approaches, PLS is especially suitable for studies with small sample size (Benitez-Amado and Walczuch, 2012;Chin et al, 2003) and consequently more appropriate for our study. Operations management journals have recently incorporated this approach in their publications (Lockstrom and Lei, 2013;Mackelprang, Jayaram and Xu, 2012;Perols, Zimmermann and Kortmann, 2013;Sawhney, 2013). Mackelprang et al (2012) give a detailed explanation of PLS usage in cases of operations management publications.…”
Section: 3structural Modelmentioning
confidence: 99%